Molecular Docking and Molecular Dynamics Study of Alcoholic Compounds as Mycobactericidal Agents Using InhA, MabA and PanK as Receptors - Syahputra, Gita; Arwansyah, Arwansyah; Kusharyoto, Wien (ANNALES BOGORIENSES, 2018)
Tuberculosis (TB) infection is one of the primaryinfectious diseases in many developing countries; even there are minor cases in some developed countries. TB infection spread through the air and ismore probable when using improper disinfectant on medical and laboratory equipment which related to TB research. The appropriate disinfectants which are commonly usedin laboratory equipment can reduce the risk of transmission of TB disease. Alcoholic compoundsare one of the common disinfectants with a broad spectrum activity towardsmicrobes,viruses, and fungus. We employed molecular docking and molecular dynamics simulation to support virtual screening and ligand-receptor complex binding observation in searching for an appropriate mycobactericidal agent.Based on the analysis of molecular docking and molecular dynamics, pentadecanol has potency as a mycobactericidal agent with PanK as itsspecific receptor. The Gibbs free energy (∆G) for the interaction of pentadecanol with PanKhas been found to be -5.5 kcal/mol. Molecular dynamics analysis at 300K and 1 atm for 5 ns showed a little change in the confirmation of the binding site, whilepentadecanolwas still being bound by its binding siteon PanK.